A porous spherical sodium fluoride adsorbent for purification of electronic grade gas and a preparation method thereof
Patent Information
- Application Number
- CN202611108483.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]本发明的目的是为了解决现有技术中存在的缺点,现有的气体提纯技术主要包括物理吸附法、化学吸附法和膜分离法等,其中物理吸附法通常依赖于多孔吸附剂对气体分子进行吸附,然而,传统的吸附剂往往存在以下几个问题:第一,吸附剂的孔隙率和球形度不稳定,导致其比表面积较小,吸附效率低;第二,吸附剂的化学纯度较低,容易在高温条件下释放有害物质,影响吸附效果;第三,吸附剂的压缩强度较差,容易在使用过程中出现颗粒破碎,降低其使用寿命;第四,传统的湿球成型和烧结工艺的温度和湿度控制较为粗糙,缺乏对微观结构的精准调控,导致最终产品性能不稳定
本发明中,通过控制浆料的黏度和湿球成型过程,使得最终制得的氟化钠吸附剂具有较高的孔隙率和良好的球形度,从而有效提高吸附剂的比表面积与气体传输效率,改善其对电子级气体的吸附性能,通过在浆料中加入3wt%的纳米二氧化硅或碳纳米管,结合表面积检测与孔径分布测试,可有效调控吸附剂的微观结构,实现孔径分布集中在25nm范围内,同时提高比表面积,优化吸附剂的气体吸附能力,通过在湿球成型过程中精确调节湿度、温度和压力,可确保球形度合格且稳定性更强,从而提高最终颗粒的均匀性和强度,保证吸附剂的性能稳定,通过使用图像识别系统实时检测湿球的球形度,确保球形度大于0.90时判定为合格颗粒,有效避免了不合格湿球对最终吸附剂球形度和结构的负面影响,从而提高吸附剂的均匀性和性能,通过精确控制烧结过程中温度、湿度、气流与气氛及微波辅助加热技术,可有效去除有机粘合剂并优化孔隙结构,进一步提高吸附剂的孔隙度和比表面积,提升其对HF气体的吸附能力,通过氧分压传感器监测炉内气氛,保持氧分压在设定范围内,确保烧结过程中有机物的完全分解,同时优化烧结过程中的孔隙形成与结构分布,确保颗粒的化学纯度高于99%,使其达到较好的吸附效果。
Abstract
Description
Technical Field
[0001] This invention relates to the field of porous spherical sodium fluoride adsorbent technology, and in particular to a porous spherical sodium fluoride adsorbent for electronic-grade gas purification and its preparation method. Background Technology
[0002] With the rapid development of the electronics industry, the purity requirements for electronic-grade gases are becoming increasingly stringent, especially in high-precision fields such as semiconductor and integrated circuit manufacturing. Impurities in gases often have a significant impact on product quality, especially the presence of harmful gases such as hydrogen fluoride (HF). Therefore, how to effectively purify electronic-grade gases and remove harmful substances has become an urgent technical challenge. Existing gas purification technologies mainly include physical adsorption, chemical adsorption, and membrane separation. Among them, physical adsorption typically relies on porous adsorbents to adsorb gas molecules. However, traditional adsorbents often have the following problems: First, the porosity and sphericity of the adsorbent are unstable, resulting in a small specific surface area and low adsorption efficiency. Second, the adsorbent has low chemical purity and is prone to releasing harmful substances under high temperature conditions, which affects the adsorption effect. Third, the adsorbent has poor compressive strength, making it prone to particle breakage during use and reducing its service life. Fourth, the temperature and humidity control of traditional wet bulb molding and sintering processes is relatively rough, lacking precise control over the microstructure, resulting in unstable performance of the final product. Summary of the Invention
[0003] The purpose of this invention is to address the shortcomings of existing technologies. Current gas purification technologies mainly include physical adsorption, chemical adsorption, and membrane separation. Physical adsorption typically relies on porous adsorbents to adsorb gas molecules. However, traditional adsorbents often suffer from the following problems: First, the porosity and sphericity of the adsorbent are unstable, resulting in a small specific surface area and low adsorption efficiency. Second, the chemical purity of the adsorbent is low, making it prone to releasing harmful substances at high temperatures, affecting the adsorption effect. Third, the compressive strength of the adsorbent is poor, easily leading to particle breakage during use and reducing its service life. Fourth, the temperature and humidity control in traditional wet-bulb forming and sintering processes is relatively coarse, lacking precise control over the microstructure, resulting in unstable performance of the final product.
[0004] To achieve the above objectives, the present invention adopts the following technical solution: a porous spherical sodium fluoride adsorbent for electronic-grade gas purification, wherein the adsorbent is composed of sodium fluoride, guar gum or hydroxypropyl methylcellulose as the main organic binder, and water mixed in a specific mass ratio, and has high porosity and good sphericity. Under the control of sintering and coating processes, the chemical purity can approach 99%, and the pressure resistance is greater than 5 MPa, and the saturated adsorption capacity for HF gas is higher than 500 mg / g.
[0005] A method for preparing porous spherical sodium fluoride adsorbent for electronic-grade gas purification includes the following steps: a) Mix sodium fluoride, guar gum or hydroxypropyl methylcellulose and water, and make the mixture into a slurry; b) The slurry is made into wet balls using compression molding or shot blasting techniques; c) In the sintering process, wet bulbs are prepared into particulate adsorbents; d) Using nanoscale surface coating technology, a nano-protective layer is formed by surface deposition of aluminum fluoride precursor as coating, and particulate adsorbent coating with a thickness of 0.1-1μm is applied.
[0006] In a preferred embodiment, the mass ratio of sodium fluoride: organic binder: water is 1:0.03-0.05:3-4, and a slurry with controllable viscosity and stability is prepared.
[0007] In a preferred embodiment, during the mixing process, a specific type of nanoscale filler or conductive material, such as nano-silica or carbon nanotubes, is introduced at a concentration of 1-5 wt%. Surface area detection or pore size distribution testing is used, and when the pore size distribution is concentrated in the range of 2-50 nm and the specific surface area reaches the design value, the microstructure control is deemed to have met the standard. Meanwhile, an online viscosity detection device is used to monitor the viscosity of the slurry in real time. During the mixing process, when the viscosity of the slurry is in the range of 500-2000 mPa·s, it is judged as a qualified slurry; otherwise, it is corrected by adjusting the amount of water added or the content of the binder.
[0008] In one preferred embodiment, the humidity, temperature, and pressure of the wet bulb are monitored in real time during the wet bulb forming process, and the temperature, humidity, and pressure are precisely adjusted. Temperature 20-30℃, humidity 80-90%, pressure 2-5MPa.
[0009] In a preferred embodiment, during the wet-bulb forming process, an image recognition system is used to monitor the sphericity of the wet-bulbs in real time. When the sphericity is ≥0.90, the particles are judged to be qualified particles; otherwise, they are reworked.
[0010] As a preferred embodiment, in the sintering process, the wet bulb is kept at 250-450℃ for 1-3 hours to remove the organic binder, and the CO2 release rate is detected according to the exhaust gas composition analysis. When the CO2 release rate tends to stabilize and is lower than the set threshold, the organic matter decomposition is determined to be complete. The gas in the sintering furnace is further adjusted so that the ratio of nitrogen, oxygen and water vapor mixture is nitrogen:oxygen:water vapor = 80:15:5 and heated to 500-800℃. The sintering process is carried out at high temperature for 1-2 hours to precisely control the pore formation process, optimize the pore distribution and structure, and produce granular adsorbent.
[0011] In a preferred embodiment, the sintering process employs airflow control technology and microwave-assisted heating technology to adjust the airflow direction and temperature distribution within the furnace, thereby controlling the temperature gradient at 20-30℃ / min. Microwave radiation is used to accelerate the decomposition of organic matter, while an oxygen partial pressure sensor is used to monitor the atmosphere within the furnace, ensuring that the oxygen partial pressure within the furnace remains within a set range of ±5%.
[0012] Compared with the prior art, the advantages and positive effects of the present invention are as follows: In this invention, by controlling the viscosity of the slurry and the wet-bulb forming process, the final sodium fluoride adsorbent exhibits high porosity and good sphericity, thereby effectively improving the specific surface area and gas transport efficiency of the adsorbent and enhancing its adsorption performance for electronic-grade gases. By adding 3 wt% nano-silica or carbon nanotubes to the slurry, combined with surface area detection and pore size distribution testing, the microstructure of the adsorbent can be effectively controlled, achieving a pore size distribution concentrated within the 25 nm range. This simultaneously increases the specific surface area and optimizes the gas adsorption capacity of the adsorbent. Precise adjustment of humidity, temperature, and pressure during the wet-bulb forming process ensures qualified sphericity and enhanced stability, thereby improving the uniformity and strength of the final particles and guaranteeing stable adsorbent performance. (See Figure...) The identification system detects the sphericity of wet bulbs in real time, ensuring that particles with a sphericity greater than 0.90 are considered qualified. This effectively avoids the negative impact of unqualified wet bulbs on the final adsorbent's sphericity and structure, thereby improving the adsorbent's uniformity and performance. By precisely controlling the temperature, humidity, airflow, atmosphere, and microwave-assisted heating technology during sintering, organic binders can be effectively removed and the pore structure optimized, further increasing the adsorbent's porosity and specific surface area, and enhancing its adsorption capacity for HF gas. The oxygen partial pressure sensor monitors the furnace atmosphere, maintaining the oxygen partial pressure within the set range to ensure the complete decomposition of organic matter during sintering. Simultaneously, it optimizes pore formation and structural distribution during sintering, ensuring that the chemical purity of the particles is higher than 99%, thus achieving better adsorption effects. Detailed Implementation
[0013] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0014] Example This invention provides a technical solution: a porous spherical sodium fluoride adsorbent for electronic-grade gas purification. The adsorbent is made of sodium fluoride, guar gum or hydroxypropyl methylcellulose as the main organic binder, and water mixed in a specific mass ratio. It has high porosity and good sphericity. Under the control of sintering and coating processes, the chemical purity can approach 99%, and the pressure resistance is greater than 5MPa. The saturated adsorption capacity for HF gas is higher than 500mg / g. A method for preparing porous spherical sodium fluoride adsorbent for electronic-grade gas purification includes the following steps: a) A mixture of sodium fluoride, hydroxypropyl methylcellulose, and water is formed, and the mixture is then made into a slurry; b) The slurry is made into wet balls using compression molding or shot blasting techniques; c) In the sintering process, wet bulbs are prepared into particulate adsorbents; d) A nanoscale surface coating technology is used to deposit a nano-protective layer with a thickness of 0.5 μm using an aluminum fluoride precursor. The mass ratio of sodium fluoride: organic binder: water is 1:0.05:3.5, and a slurry with controllable viscosity and stability is prepared. During the mixing process, specific types of nanoscale fillers or conductive materials such as nano-silica or carbon nanotubes are introduced at a concentration of 1-5 wt%. Surface area detection or pore size distribution testing is used. When the pore size distribution is concentrated in the range of 25 nm and the specific surface area reaches the design value, the microstructure control is deemed to have met the standard. Meanwhile, an online viscosity detection device is used to monitor the viscosity of the slurry in real time. During the mixing process, when the viscosity of the slurry is within the range of 1200 mPa·s, it is judged as a qualified slurry; otherwise, it is corrected by adjusting the amount of water added or the content of the binder. Through the above embodiments, by mixing sodium fluoride, hydroxypropyl methylcellulose and water in a certain proportion and introducing nanoscale fillers or conductive materials, the viscosity and stability of the slurry can be adjusted to improve the molding effect and enhance the particle quality. During the wet-bulb molding process, the humidity, temperature, and pressure of the wet bulb are monitored in real time, and the temperature, humidity, and pressure are precisely adjusted. Temperature 25℃, humidity 85%, pressure 3MPa; During the wet bulb forming process, an image recognition system is used to monitor the sphericity of the wet bulbs in real time. When the sphericity is greater than 0.90, the pellets are judged to be qualified; otherwise, they are reworked. Through the above embodiments, by real-time monitoring of the humidity, temperature and pressure of the wet bulbs, and precise control of these process parameters, the effect of uniform wet bulb molding and excellent sphericity can be achieved, thereby ensuring the stability and uniformity of the final particles. In the sintering process, wet bulbs are kept at 350°C for 2 hours to remove organic binders, and the CO2 release rate is detected by analyzing the exhaust gas composition. When the CO2 release rate tends to stabilize and is lower than the set threshold, the organic matter decomposition is considered complete. The gas in the sintering furnace was further adjusted so that the ratio of nitrogen, oxygen and water vapor mixture was 80:15:5 and heated to 650°C. The sintering process was carried out at the high temperature for 1.5 hours to precisely control the formation process of pores, optimize the distribution and structure of pores, and produce granular adsorbent. In the sintering process, airflow control technology and microwave-assisted heating technology are used to adjust the airflow direction and temperature distribution in the furnace, so that the temperature gradient is controlled at 25℃ / min. Microwave radiation is used to accelerate the decomposition of organic matter, and an oxygen partial pressure sensor is used to monitor the atmosphere in the furnace, so that the oxygen partial pressure in the furnace is maintained within the set range of ±5%. From a testing perspective, the final adsorbent mainly contains two types of components: one is the soluble sodium fluoride main component, and the other is the insoluble inorganic structure-regulating component, such as nano-silica. Since silica exists primarily as an insoluble substance in aqueous systems, the determination of F is performed after dissolving it in water. - The content method essentially measures the content of soluble sodium fluoride in the sample, rather than evaluating the total purity of all solid particles. Therefore, the adsorbent contains 95.8 wt% soluble sodium fluoride and 3.2 wt% nano-silica. Through the above embodiments, by sintering wet pellets at 350°C and monitoring the CO2 release rate, the complete decomposition of the organic binder is ensured, thereby improving the chemical purity and stability of the particles. By adjusting the gas ratio and temperature control during the sintering process, the pore structure of the particles is optimized, thereby improving the porosity and adsorption performance of the adsorbent. By adopting airflow control technology and microwave-assisted heating technology, the temperature gradient during the sintering process is made uniform, and by precisely controlling the atmosphere, the microstructure of the particles is optimized and the product performance is improved. By controlling the viscosity of the slurry and the wet-bulb forming process, the final sodium fluoride adsorbent has high porosity and good sphericity, thereby effectively improving the specific surface area and gas transport efficiency of the adsorbent and enhancing its adsorption performance for electronic-grade gases. By adding 3wt% nano-silica or carbon nanotubes to the slurry, combined with surface area detection and pore size distribution testing, the microstructure of the adsorbent can be effectively controlled, achieving a pore size distribution concentrated in the range of 25nm, while increasing the specific surface area and optimizing the gas adsorption capacity of the adsorbent. By precisely adjusting humidity, temperature, and pressure during the wet bulb molding process, it is possible to ensure that the sphericity is qualified and the stability is stronger, thereby improving the uniformity and strength of the final particles and ensuring the stable performance of the adsorbent. By using an image recognition system to detect the sphericity of wet bulbs in real time, particles with a sphericity greater than 0.90 are considered qualified. This effectively avoids the negative impact of unqualified wet bulbs on the sphericity and structure of the final adsorbent, thereby improving the uniformity and performance of the adsorbent. By precisely controlling the temperature, humidity, airflow and atmosphere, and microwave-assisted heating technology during the sintering process, organic binders can be effectively removed and the pore structure optimized, further improving the porosity and specific surface area of the adsorbent and enhancing its adsorption capacity for HF gas. An appropriate amount of water vapor can help control the atmosphere inside the furnace, thereby affecting the chemical reaction and physical properties of the material. The presence of water vapor can reduce the occurrence of oxidation reactions and help maintain the chemical stability of the material. Water vapor can promote the diffusion of gas at high temperatures, thereby improving the contact efficiency between gaseous reactants and adsorbents and enhancing the preparation quality of the adsorbent. The atmosphere inside the furnace is monitored by an oxygen partial pressure sensor to keep the oxygen partial pressure within a set range, ensuring the complete decomposition of organic matter during sintering. At the same time, the formation and structural distribution of pores during sintering are optimized to ensure the chemical purity of the particles and achieve better adsorption effect. Through the above embodiments, the use of nanoscale fillers such as nano-silica has excellent strength and toughness, which can significantly improve the mechanical properties of the adsorbent, making it less prone to breakage during compression and use.
[0015] The working principle of this embodiment: Sodium fluoride: organic binder (guar gum or hydroxypropyl methylcellulose): water = 1:0.03-0.05:3-4. Mix sodium fluoride, guar gum (or hydroxypropyl methylcellulose) and water to form a homogeneous mixture. The mixture is prepared into a slurry with controllable viscosity and stability, ensuring that the viscosity of the slurry is within the range of 500-2000 mPa·s. At this point, an online viscosity meter is used to monitor the slurry viscosity to ensure that it meets the requirements. During the mixing process, specific types of nanoscale fillers (such as nano-silica or carbon nanotubes) are added, with the concentration controlled at 1-5 wt%. Use surface area detection or pore size distribution testing equipment to ensure that the pore size distribution is concentrated in the range of 2-50 nm and that the specific surface area meets the design requirements, so as to ensure that the microstructure control meets the standards. The slurry is formed into wet balls using compression molding or shot blasting techniques. During the wet bulb molding process, the humidity, temperature and pressure of the wet bulb are monitored in real time to ensure that the temperature is between 20-30℃, the humidity is controlled at 80-90%, and the pressure is within the range of 2-5 MPa. The sphericity of the wet bulb is monitored in real time using an image recognition system to ensure that the sphericity is ≥0.90. If it does not meet the requirements, rework is required. The wet bulbs are placed in a sintering furnace and held at 250-450℃ for 1-3 hours to remove the organic binder. The CO2 release rate is then detected by analyzing the exhaust gas composition. When the CO2 release rate stabilizes and falls below a set threshold, the organic binder is considered to have decomposed completely. The gas composition inside the sintering furnace was further adjusted, with the mixing ratio of nitrogen, oxygen and water vapor being 80:15:5. The furnace was then heated to 500-800℃ for a sintering process of 1-2 hours.
[0016] During the sintering process, the formation of pores is precisely controlled, and the distribution and structure of pores are optimized to form particulate adsorbents. Using nanoscale surface coating technology, a nano protective layer is formed by surface deposition of a precursor containing aluminum fluoride. The precursor is then adapted to improve dispersibility and interfacial adhesion. Finally, the nano coating is uniformly coated on the surface of the adsorbent by suspension stirring.
[0017] The particulate adsorbent is coated with a layer of 0.1-1 μm thickness to enhance its chemical stability and improve its gas adsorption performance; During the sintering process, airflow control technology and microwave-assisted heating technology are used to adjust the airflow direction and temperature distribution in the furnace to ensure that the temperature gradient in the furnace is controlled within the range of 20-30℃ / min. Microwave radiation is used to accelerate the decomposition of organic matter, and an oxygen partial pressure sensor is used to monitor the atmosphere inside the furnace to ensure that the oxygen partial pressure inside the furnace is maintained within the set range (±5%).
[0018] Performance testing Example 1 In this embodiment: the adsorbent was prepared according to the above method, with 3wt% nano-silica added to the slurry. The wet bulb forming temperature was 25℃, humidity was 85%, pressure was 3MPa, sintering was carried out at 650℃, and a 0.5μm aluminum fluoride coating was applied. The test results showed that the adsorbent had a dynamic adsorption capacity of 502mg / g for HF gas, a sphericity of 0.92, a specific surface area that met the design value, and a chemical purity of 99%. Comparative Example 1 Comparative Example 1 is prepared under the same conditions as Example 1, but without the addition of nanofillers or the application of a coating. Test results show that the HF adsorption capacity is 395 mg / g, the sphericity is 0.85, the specific surface area is relatively low, and the adsorption performance is significantly lower than that of Example 1.
[0019] Comparative Example 2 Comparative Example 2 is largely the same as the method of Example 1 provided, except that: after the sintering of the particulate adsorbent, no nano-protective layer coating treatment was performed. The test showed that the HF adsorption performance was not significantly improved, and the coating stability was slightly lower than that of the aluminum fluoride coating, which proves the rationality of choosing the aluminum fluoride coating in this invention.
[0020] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any other way. Any person skilled in the art may make changes or modifications to the above-disclosed technical content to create equivalent embodiments for application in other fields. However, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the protection scope of the present invention.
Claims
1. A porous spherical sodium fluoride adsorbent for electronic-grade gas purification, characterized in that, The adsorbent is made by mixing sodium fluoride, guar gum or hydroxypropyl methylcellulose as the main organic binder and water in a specific mass ratio. It has high porosity and good sphericity. Under the control of sintering and coating processes, the chemical purity can be close to 99%, and the pressure resistance is greater than 5 MPa. The saturated adsorption capacity for HF gas is higher than 500 mg / g.
2. A method for preparing porous spherical sodium fluoride adsorbent for electronic-grade gas purification, characterized in that, Includes the following steps: a) Mix sodium fluoride, guar gum or hydroxypropyl methylcellulose and water, and make the mixture into a slurry; b) The slurry is made into wet balls using compression molding or shot blasting techniques; c) In the sintering process, wet bulbs are prepared into particulate adsorbents; d) A nanoscale surface coating technology is used to deposit a nano-protective layer with a thickness of 0.1-1 μm using an aluminum fluoride precursor.
3. The method for preparing porous spherical sodium fluoride adsorbent for electronic-grade gas purification according to claim 2, characterized in that, The mass ratio of the mixture is sodium fluoride: organic binder: water = 1:0.03-0.05:3-4, and a slurry with controllable viscosity and stability is prepared.
4. The method for preparing porous spherical sodium fluoride adsorbent for electronic-grade gas purification according to claim 3, characterized in that, During the mixing process, a specific type of nanoscale filler or conductive material, such as nano-silica or carbon nanotubes, is introduced at a concentration of 1-5 wt%. Surface area detection or pore size distribution testing is used. When the pore size distribution is concentrated in the range of 2-50 nm and the specific surface area reaches the design value, the microstructure control is deemed to have met the standard. Meanwhile, an online viscosity detection device is used to monitor the viscosity of the slurry in real time. During the mixing process, when the viscosity of the slurry is in the range of 500-2000 mPa·s, it is judged as a qualified slurry; otherwise, it is corrected by adjusting the amount of water added or the content of the binder.
5. The method for preparing porous spherical sodium fluoride adsorbent for electronic-grade gas purification according to claim 2, characterized in that, During the wet-bulb forming process, the humidity, temperature, and pressure of the wet bulb are monitored in real time, and the temperature, humidity, and pressure are precisely adjusted. Temperature 20-30℃, humidity 80-90%, pressure 2-5MPa.
6. The method for preparing a porous spherical sodium fluoride adsorbent for electronic-grade gas purification according to claim 5, characterized in that, During the wet-bulb forming process, an image recognition system is used to monitor the sphericity of the wet-bulbs in real time. When the sphericity is ≥0.90, the particles are judged to be qualified particles; otherwise, they are reworked.
7. The method for preparing a porous spherical sodium fluoride adsorbent for electronic-grade gas purification according to claim 2, characterized in that, In the sintering process, wet bulbs are kept at 250-450℃ for 1-3 hours to remove organic binders. The CO2 release rate is detected by analyzing the exhaust gas composition. When the CO2 release rate tends to stabilize and is below the set threshold, the organic matter decomposition is considered complete. The gas in the sintering furnace is further adjusted, with the ratio of nitrogen, oxygen and water vapor being nitrogen:oxygen:water vapor = 80:15:5, and heated to 500-800℃. The sintering process is carried out at high temperature for 1-2 hours to precisely control the pore formation process, optimize the pore distribution and structure, and produce granular adsorbent.
8. The method for preparing a porous spherical sodium fluoride adsorbent for electronic-grade gas purification according to claim 7, characterized in that, The sintering process employs airflow control technology and microwave-assisted heating technology to adjust the airflow direction and temperature distribution within the furnace, thereby controlling the temperature gradient at 20-30℃ / min. Microwave radiation is used to accelerate the decomposition of organic matter, while an oxygen partial pressure sensor is used to monitor the atmosphere within the furnace, maintaining the oxygen partial pressure within the furnace within a set range of ±5%.